Spiral Bit-string Representation of Color for Image Retrieval - Abdelhamid, Abdesselam; Wang, Hui Hui; Narayanan, Kulathu Ramaiyer (The International Arab Journal of Information Technology, 2010)
This paper describes a color-based image retrieval technique that uses a new representation for the color content of an image. The new representation, called Spiral Bit-string Representation, is an extension of the traditional bitmap signature representation, where the image description is performed in a spiral manner, starting from the centre of the image and moving clockwise towards the border. The major advantages of this representation are its simplicity, its suitability for retrieval of rotated and scaled images as well as for sub-image querying.